A interação escolar de uma criança com Sindrome de Tourette, segundo as percepções de pais e educadores um estudo de caso exploratório - Terra, Ana Paula de Alvarenga [UNESP]; Rondina, Regina de Cássia [UNESP] (Universidade de São Paulo. Agência de Bibliotecas e Coleções Digitais, 2014)
The syndrome of Gilles de la Tourette (ST) can cause marked distress in several areas of functioning. The literature indicates that children with TS may present diffi culties in relationships with teachers and peers. This case study exploration aimed to discover and describe the perceptions of parents and teachers of child with TS enrolled in regular school, regarding the child-school relationships. Interviews were conducted with parents of a 8 years-old child, diagnosed with ST and three educators. Participant observation of everyday children’s school was also performed. The set of reports reveals doubts on the part of respondents to identify involuntary behaviors of the child or to identify intentional actions. It was observed that there is still no connection between parents and educators in meeting the needs of the child. It is assumed that intervention strategies in a multidisciplinary perspective could help parents, educators and health care professionals act in a coordinated way in order to improve the school and social interaction of the child.

A Síndrome de Gilles de La Tourette (ST) pode gerar acentuado sofrimento em diversas áreas da vida do indivíduo. A literatura refere que a criança com ST pode apresentar difi culdades no relacionamento com educadores e colegas. O objetivo deste estudo de caso exploratório visou conhecer e descrever as percepções de pais e educadores sobre aspectos da dinâmica de interação escolar de uma criança com ST, matriculada no ensino fundamental regular. Foram realizadas entrevistas com os pais de uma criança de 8 anos de idade diagnosticada com ST e com três educadores. Foram também realizadas sessões de observação participante do cotidiano escolar. O conjunto dos relatos revela dúvidas por parte dos entrevistados, no sentido de identifi car comportamentos involuntários da criança ou de identifi car ações intencionais. Observou-se que ainda não existe articulação entre pais e educadores no atendimento às necessidades da criança. Supõe-se que estratégias de intervenção em perspectiva multiprofi ssional poderiam contribuir para que pais, educadores e profi ssionais de saúde atuem de forma articulada, no sentido de promover melhorias na interação escolar e social da criança.
Scholar interaction of a child whith Tourette disorder by the perspective of parents and educators: case study exploration
Keywords: Sindrome de Tourette; interação escolar; ensino fundamental